Principle Analysis and Dynamic Simulation of Self-stabilizing Speed Transmission for Wind Turbine - Su Rui; Li Gangjun; Rui Xiaoming (Jixie chuandong)
A novel self-stabilizing speed transmission used for wind power generation is proposed. It can keep the constant speed of synchronous generator amature under the time-varying speed of wind rotor. The self-stabilizing speed transmission consist of differential gear train,differential mechanism and constant speed motor. The time-varying speed of wind rotor and constant speed of motor are superimposed by the left wheel and right wheel of differential mechanism. The shell of differential mechanical can automatically adjust the output speed of differential gear train to stable. The kinematics analysis for the self-stabilizing speed wind turbine is carried out,and the mass-spring-damper model of the transmission is established for three shafts system with double inputs and single output. The simulation is executed in SIMULINK software with turbulent wind input.The influences on output shaft speed and torque under different inertia,stiffness,damping are discussed. The frequency of the output shaft speed is compared with natural frequency in order to evaluate the possibility of the system resonance.